2012
DOI: 10.1186/1476-9255-9-31
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline impairs neutrophil migration to the airspaces of the lung in mice exposed to intratracheal lipopolysaccharide

Abstract: BackgroundTetracyclines are broad-spectrum antibiotics that are also used to induce gene expression using the reverse tetracycline transactivator / tetracycline operator system (rtTA/tetO system). The system assumes that tetracyclines have no effects on mammals. However, a number of studies suggest that tetracyclines may have powerful anti-inflammatory effects. We report that the tetracycline, doxycycline, inhibits neutrophil (PMN) influx into the lungs of mice treated with bacterial endotoxin (LPS).MethodsMic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…Inhibition of neutrophil infiltration and MMP activity by doxycycline markedly reduced susceptibility to AD and rupture in Lnk -/mice. The tetracycline antibiotic doxycycline potently inhibits a broad range of MMPs by binding the zinc-containing active site (6) and inhibits neutrophil activity and migration (7,8). To test the hypothesis that both neutrophils and MMP activity are important in the development of AD, we treated Lnk -/mice with doxycycline at 100 mg/kg/day, a dose that achieves plasma levels in mice comparable to levels in humans treated with doxycycline (9), prior to and during Ang II infusion ( Figure 6A).…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of neutrophil infiltration and MMP activity by doxycycline markedly reduced susceptibility to AD and rupture in Lnk -/mice. The tetracycline antibiotic doxycycline potently inhibits a broad range of MMPs by binding the zinc-containing active site (6) and inhibits neutrophil activity and migration (7,8). To test the hypothesis that both neutrophils and MMP activity are important in the development of AD, we treated Lnk -/mice with doxycycline at 100 mg/kg/day, a dose that achieves plasma levels in mice comparable to levels in humans treated with doxycycline (9), prior to and during Ang II infusion ( Figure 6A).…”
Section: Resultsmentioning
confidence: 99%
“…The BALF was then centrifuged at 300 g for 10 min, and the supernatant and cell pellet were collected. The number of leukocytes in the pellet was counted using an automated hematology analyzer (KX-21N; Sysmex Corporation; Moon et al, 2012 ). BALF was stored at −80°C until use.…”
Section: Methodsmentioning
confidence: 99%
“…Despite these robust effects on MMP-9, doxycycline did not change CRP levels in the serum or inflammatory cytokine levels in the sputum. Although previous literature utilising in vitro and in vivo models have suggested that doxycycline has an effect on inflammatory cytokine expression [30,31], clinical trials have also failed to observe these findings [32,33]. There was also no difference in change of This study demonstrated a reduction in total hospital days for the doxycycline participants, although this result may have been affected by non-clinical factors such as a patient's ability to complete therapies at home versus hospital.…”
Section: Discussionmentioning
confidence: 55%